2004
DOI: 10.1080/09595230412331324581
|View full text |Cite
|
Sign up to set email alerts
|

Implementing integrated treatment for co‐existing substance use and severe mental health problems in assertive outreach teams: training issues

Abstract: This study sought to evaluate systematically training and implementation of a specific integrated treatment approach for co-occurring problem substance use and mental health within existing assertive outreach (AO) teams. The AO team was treated as a whole unit rather than as individual clinicians. They were provided with training and supervision to deliver a cognitive--behavioural integrated treatment approach. In a quasi-experimental time-lag design three teams were trained immediately and two others after an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 19 publications
3
23
0
1
Order By: Relevance
“…The DoH (2002) have stated that in order to perpetuate the use and adaptation of substance misuse techniques 'Ongoing supervision is crucial to ensure that new ideas are embedded in daily work and that staff feel supported in their practice'. This study supports findings from UK research by Graham (2004), Holland (1998) and Maslin et al (2001) that training has a significant impact on psychiatric practitioners' skills and confidence in working with dual diagnosis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The DoH (2002) have stated that in order to perpetuate the use and adaptation of substance misuse techniques 'Ongoing supervision is crucial to ensure that new ideas are embedded in daily work and that staff feel supported in their practice'. This study supports findings from UK research by Graham (2004), Holland (1998) and Maslin et al (2001) that training has a significant impact on psychiatric practitioners' skills and confidence in working with dual diagnosis.…”
Section: Discussionsupporting
confidence: 92%
“…However, the results show that few of the study participants had any addiction work experience. The number of participants who indicated they had either had a placement or had worked in drug and/or alcohol teams was small and is in line with findings from other studies (Graham, 2004;Holland, 1998).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This result is encouraging given the fact that previous studies showed specific training programmes to be successful in improving practitioners' DD competency levels [9,10] . It has been widely acknowledged that the treatment needs of individuals with co-morbidity are heterogeneous and often require coordination of multiple interventions.…”
Section: Discussionmentioning
confidence: 53%
“…Participants in the current study belonged to teams that had received training in an integrated treatment approach (Graham, 2004;Graham et al, 2004) and have ongoing support to facilitate its implementation. Integrated treatment approaches aim to integrate substance-use problems into the routine treatment of psychosis.…”
Section: Discussionmentioning
confidence: 99%